Efficacy and safety of combining tislelizumab with capecitabine compared to capecitabine alone in the adjuvant treatment of biliary tract cancers: rationale and protocol design for a randomized clinical trial - Xubiao Wei; Yabo Jiang; Jinxue Zhou; Hongkun Zhou; Dong Qu; Xiaofei Ye; Yaxin Zheng; Shuqun Cheng (BMC Cancer)
Abstract Background Adjuvant therapy with capecitabine is recommended to improve survival for resectable biliary tract cancers (BTC) patients. Considering that the combination of PD-1/PD-L1 inhibitors with chemotherapy has demonstrated a survival benefit over chemotherapy alone in advanced stage BTC, we aim to evaluate the treatment efficacy and safety of tislelizumab, a PD-1 inhibitor, combined with capecitabine vs. capecitabine alone as an adjuvant treatment in patients with resectable BTC. Method This multicenter randomized controlled study will include a total of 140 patients who will have undergone curative resection within 4 weeks prior to enrollment and will have been pathologically diagnosed with cholangiocarcinoma (including intrahepatic and extrahepatic cholangiocarcinoma) or muscle-invasive gallbladder carcinoma. Those patients will be randomly assigned 1:1 to tislelizumab combined with capecitabine or capecitabine alone group. The primary endpoint will be recurrence free survival (RFS), the secondary endpoints will be overall survival (OS) and adverse events (AEs). Multi-omics biomarkers will be assessed as exploratory objective. Discussion There remains a major unmet need for more effective adjuvant therapies for resectable BTC. If this study demonstrates that adding tislelizumab enhances the therapeutic efficacy of capecitabine, this combined regimen will potentially improve the prognosis of patients with resectable BTC. In addition, we will analyze the relationship between various gene expression profiles and clinical endpoint events to define the ideal patient population receiving adjuvant immunotherapy.